2003
DOI: 10.1177/009286150303700105
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines for Assessing the Clinical Significance of Health-Related Quality of Life Changes within Clinical Trials

Abstract: Health-related quality of life (HRQOL) assessment is becoming common practice in many clinical trials. There is much debate over how to determine the clinical significance of changes in size, which applies a common statistical premise known as the empirical rule, is also presented.The review of these techniques indicates that there is no singie, optimal solution to determin--

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(177 citation statements)
references
References 20 publications
1
173
1
1
Order By: Relevance
“…For descriptive purposes, proportions of explained variance of variables other than presence of comorbidities were grouped into "disease-related" and "sociodemographic" variables. Clinical significance of differences in HRQOL outcomes was also evaluated in this study, defined as at least eight points on each SF-36 scale [24]. Statistical significance for SF-36 scales was Bonferroni corrected to account for multiple testing.…”
Section: Resultsmentioning
confidence: 99%
“…For descriptive purposes, proportions of explained variance of variables other than presence of comorbidities were grouped into "disease-related" and "sociodemographic" variables. Clinical significance of differences in HRQOL outcomes was also evaluated in this study, defined as at least eight points on each SF-36 scale [24]. Statistical significance for SF-36 scales was Bonferroni corrected to account for multiple testing.…”
Section: Resultsmentioning
confidence: 99%
“…This criterion was based on Sloan et al, who showed through their research that for any patientreported outcome instrument, a difference of half an SD can be considered clinically significant. 36,37 Equivalency was declared if a 90% CI of the difference between patients and caregivers was inside our reference CI of (À0.5SD, þ0.5SD). This reference CI was constructed based on the SD of the mean scores for the patients used as reference group.…”
Section: Testing For Equivalencymentioning
confidence: 99%
“…While palliative surgery poses some unique dilemmas within the larger scope of palliative care research, even these barriers can usually be overcome with well-constructed studies carried out by thoughtful research teams (12,13). Indeed, the methodological difficulties in palliative care research are all surmountable through existing techniques and appropriately careful scientific design (14). Communication that these hurdles can be surmounted remains a barrier to the implementation in palliative care settings.…”
Section: Dilemmas and Barriers To Palliative Care Researchmentioning
confidence: 99%